2015
DOI: 10.1128/aem.02491-15
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Response of Clostridium ljungdahlii to Oxygen Exposure

Abstract: cClostridium ljungdahlii is an important synthesis gas-fermenting bacterium used in the biofuels industry, and a preliminary investigation showed that it has some tolerance to oxygen when cultured in rich mixotrophic medium. Batch cultures not only continue to grow and consume H 2 , CO, and fructose after 8% O 2 exposure, but fermentation product analysis revealed an increase in ethanol concentration and decreased acetate concentration compared to non-oxygen-exposed cultures. In this study, the mechanisms for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 106 publications
(132 reference statements)
2
53
0
Order By: Relevance
“…These results are in contrast to what was expected, since stress causes a slower metabolism, while ethanol production by C . ljungdahlii is often induced by stress from, for instance, a low pH or oxygen exposure [41, 57]. Our findings, therefore, might reflect different growth characteristics of the planktonic and the biofilm cells.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…These results are in contrast to what was expected, since stress causes a slower metabolism, while ethanol production by C . ljungdahlii is often induced by stress from, for instance, a low pH or oxygen exposure [41, 57]. Our findings, therefore, might reflect different growth characteristics of the planktonic and the biofilm cells.…”
Section: Resultsmentioning
confidence: 84%
“…In addition, rubrerythrin, a non-haem Fe protein reported to be involved in the response of C . ljungdahlii to oxygen stress [41], was upregulated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Through transcriptome analysis, it was possible to reveal the level of transcriptional expression of genes related to the WL pathway and the energy conservation system in acetogens under autotrophic conditions [ 36 , 105 , 106 , 107 , 108 , 109 , 110 ]. In addition, ribosome profiling in C. ljungdahlii or E. limosum revealed that translational regulation of genes in the carbonyl-branch or energy conservation system is critical to their autotrophic growth [ 111 , 112 ].…”
Section: Synthetic Biology Approach On Acetogensmentioning
confidence: 99%
“…Our model system uses Clostridium ljungdahlii OTA1 to convert CO from syngas as its sole carbon source into ethanol and acetate (Koepke et al, 2011; Ragsdale and Pierce, 2008; Tanner et al, 1993). Mutant OTA1 was derived from ATCC 55383 and isolated for its desirable ethanol to acetate ratio and CO consumption (Tirado-Acevedo, 2010; Whitham et al, 2015). Wild type C. ljungdahlii has been shown to have a maximum specific uptake of ~35 mmol CO g DCW −1 h −1 in liquid culture (Mohammadi et al, 2014; Richter et al, 2013).…”
Section: Introductionmentioning
confidence: 99%